Prognostic Value of the Global Left Ventricular Contractility Index in Patients with Severe Mitral Regurgitation and Preserved Left Ventricular Ejection Fraction - Tony Li; Vinay B. Panday; Jessele Lai; Nicholas Gao; Beth Lim; Aloysius Leow; Sarah Tan; Quek Swee Chye; Ching Hui Sia; William Kong; Tiong Cheng Yeo; Ru San Tan; et al. (Journal of Cardiovascular Development and Disease)
Introduction: Assessment of left ventricular (LV) systolic function is important in valvular heart disease. The global LV contractility index, dσ*/dtmax, is load-independent and has been reported to be associated with clinical outcomes in heart failure and aortic stenosis. We aim to assess if dσ*/dtmax could predict adverse outcomes in patients with severe mitral regurgitation (MR). Methodology: We studied dσ*/dtmax in a cohort of 127 patients with isolated severe primary MR and preserved LVEF ≥ 60%. Patients with prior valvular intervention or concurrent valvular disease were excluded. We tested dσ*/dtmax against a composite of adverse outcomes including all-cause mortality, heart failure hospitalization, and mitral valve intervention. Results: The cohort had a mean age of 58 years old and was predominantly male. Of the 127 patients, eight (6.3%) needed subsequent hospitalization for heart failure, while 30 (23.6%) and 11 (8.7%) patients underwent mitral valve repair and replacement, respectively, And 14 (11.0%) passed away. Of the patients (n = 54 (42.5%)) who had an adverse outcome during follow-up, dσ*/dtmax demonstrated an independent association with composite adverse outcome, including its individual components. On ROC analysis, a cut-off of 2.15 s−1 was identified. Based on this cut-off, dσ*/dtmax retained an independent association with composite adverse outcome after adjusting for covariates including age, sex, ischemic heart disease, pulmonary artery systolic pressure, and left ventricular end systolic diameter. Conclusions: In patients with severe primary MR and preserved LVEF, reduced dσ*/dtmax was an independent predictor of adverse outcomes. It can be a useful addition to the armamentarium for assessing patients with severe MR.